2020
DOI: 10.1182/blood-2020-137713
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Amlodipine in Preventing Myocardial Iron Overload in Patients with Transfusion-Dependent Thalassemia Major : A Systematic Review and Meta-Analysis

Abstract: Background: Patients diagnosed with thalassemia major who are transfusion dependant, have iron accumulation leading to iron toxicity and severe impairment in organs like heart, liver and endocrine organs which are highly sensitive to iron toxicity. This makes iron chelation therapy imperative for these patients. Half of the deaths resulting from iron toxicity related complications are attributed to cardiac complications. Iron chelation therapies have not been completely successful to prevent iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…It is worth mentioning that our study did not report liver T2* as it was reported in only two studies, with one measuring it at 6 months (Khaled et al 10 ) and the other at 12 months (Eghbali et al 22 ), so we could not pool them together. This outcome was reported by a previous meta‐analysis, and the results were non‐significant 13 …”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…It is worth mentioning that our study did not report liver T2* as it was reported in only two studies, with one measuring it at 6 months (Khaled et al 10 ) and the other at 12 months (Eghbali et al 22 ), so we could not pool them together. This outcome was reported by a previous meta‐analysis, and the results were non‐significant 13 …”
Section: Discussionsupporting
confidence: 52%
“…T A B L E 3 Summary of previous meta-analyses Sadaf et al 18 Kashyap et al 13 Alali et al 30 Elfaituri et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gambaran studi yang dilakukan di fasilitas kesehatan primer menemukan kejadian probable sakit perut sebesar 1,8% dan nausea 3,4% akibat amlodipin [49]. Deteksi ESO oleh Khalid tahun 2019 dengan kejadian frekuensi 6 kali sakit perut juga pernah dilaporkan [50].…”
Section: Efek Sampingunclassified